P1600KIDNEY PERFUSION WITH MESENCHYMAL STROMAL CELLS OR EXTRACELLULAR VESICLES PREVENTS ISCHAEMIC DAMAGE THROUGH CD73/ADO SYSTEM IN A RAT MODEL OF DCD DONATION. (6th June 2020) - Grignano, Maria Antonietta; Bruno, Stefania; Tapparo, Marta; Iadarola, Paolo; Gregorini, Marilena; Libetta, Carmelo; Avanzini, Maria Antonietta; Viglio, Simona; Cagnone, Maddalena; Pattonieri, Eleonora Francesca; Esposito, Pasquale; RAmpino, Teresa
Abstract: Background and Aims: Adenosine (Ado), the main substrate of ATP, is a potent endogenous anti-inflammatory nucleoside. Hypoxia induces ATP depletion, AMP extracellular increase that is phosphohydrolyzed to ADO by the enzyme ecto-5′-nucleotidase (CD73). Constitutive CD73 expression is higher in deep cortex outer medulla that is the most vulnerable region to ischemic injury. Notably CD73 is also expressed on Mesenchymal Stromal Cell (MSC) and is essential phenotypic marker. Previously in a rat model of Donation after Circulatory Death (DCD), we demonstrated that the perfusion of ischemic kidney with MSC or MSC derived Extracellular Vesicles (EV) protects tissue up regulating mitochondrial energetic metabolism genes. The aim of this study was to investigate the role of CD73/Ado system in MSC/EV protection from ischemia. Method: Fisher rats were used as kidney donors and Lewis rats as MSC donors. MSC missing CD73 were produced by electroporation in the presence of specific siRNA to block CD73 expression (siMSC). EV were isolated from supernatants of MSC and siMSC (siEV) medium through differential ultracentrifugations. Size distribution and enumeration analysis were performed using NanoSight NS300. EV phenotypic characterization was performed in flow cytometer using CD45, CD49e, CD63, CD9, CD81 and CD73 monoclonal antibodies. DCD model was obtained by renal artery clamping for 20 minutes. This warm ischemia time represents the "no touch period" imposed by the Italian law to death declaration. After nephrectomy, kidneys were perfused in hypothermia (4°C) with Belzer Solution (BS), or BS supplemented with 3x106 MSC (MSC) or BS supplemented with 28, 5x109 EV/siEV (EV/siEV). The effluent fluid (EF) was collected at the beginning (T0), every hours (T1, T2, T3) and at the end of the perfusion (T4). Ado and ATP determinations in EF and tissues were performed by HPLC and ELISA, respectively. Results: EF Ado was significantly higher in MSC vs BS from T1 and in EV vs BS from T0 to T4 (p<0, 05). Only in EV, EF Ado concentration increased over time from T2 to T4 ( p<0, 05), while in BS, MSC and siEV there was a steady trend over time. There was a negative correlation between EF and tissue levels of Ado (r=0, 67 p=0, 01). Tissue ATP was higher in EV and significantly in MSC vs BS (p<0, 01). There was a negative correlation between tissue ATP and EF ADO levels (r= 0, 79 p< 0, 0001). Tissue ATP/Ado ratio was significantly higher in EV vs BS (p<0, 01). There was a negative correlation between tissue ATP/Ado ratio and EF Ado (r= 0, 84 p < 0.0001). siEV cancelled EV effects on ATP and Ado levels in EF and renal tissue. Conclusion: CD73 expressed on MSC /EV impacts on cell energy metabolism pathway and ATP generation. This is the first evidence that MSC/EV act through CD73/Ado system to prevent ischaemic damage.